Analysis of Psychomotor Abilities and Their Influence on The Work Readiness of Vocational Students in The Industrial World - Mulyono, Wahyu Dwi; Suparji, Suparji; Prawira Adistana, Gde Agus Yudha; Suryaman, Heri; Artaningtyas, Desy Ratna (TEM Journal, 2025)
Vocational High Schools (VHS) aim to produce graduates who are prepared for the workforce, however in practice, the unemployment rate among VHS graduates remains high. Psychomotor skills are important for VHS students. This study's objective was to analyze the psychomotor skills needed by VHS students and their influence on work readiness. This research is quantitative research with an ex post facto approach. Final-year VHS Building Information Modeling and Design Program students in the "Gerbangkertosusila" region (Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, and Lamongan) in East Java, Indonesia, served as the study's subjects. Questionnaires and observation sheets were used as data collection techniques. Data analysis using descriptive and path analysis. The study's findings support the notion that in order to improve students' work preparedness, psychomotor skills must be developed through instruction that aligns with industry demands.